2019
DOI: 10.5489/cuaj.5892
|View full text |Cite
|
Sign up to set email alerts
|

How far are they coming from?

Abstract: Introduction: In the province of Quebec, eight pediatric urologists practice in three tertiary centres covering large territories. To improve the availability of pediatric urology to distant families and to reduce the economic burden on them, we examined the chart of all patients attending the pediatric urological outpatient clinic. Our objectives were to evaluate the distance travelled by each urological pediatric outpatient and to report the most frequent urological referral complains. Methods: From Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…For instance, we recently reported that uro-pediatric patients travelled, on average, a 69 km distance one way for a urological visit at our center. 5 It seems reasonable that many parents would have chosen telemedicine from the 58.5% of pediatrics appointments judged as SCM by pediatric urologists. This shows that telemedicine probably would be optimal in more than our reported ratio of CCM.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we recently reported that uro-pediatric patients travelled, on average, a 69 km distance one way for a urological visit at our center. 5 It seems reasonable that many parents would have chosen telemedicine from the 58.5% of pediatrics appointments judged as SCM by pediatric urologists. This shows that telemedicine probably would be optimal in more than our reported ratio of CCM.…”
Section: Discussionmentioning
confidence: 99%
“…15 Pediatric urology patients in Quebec, Canada, travel a mean of 70 km one way for their clinic appointments, but those from farther away can travel in excess of 1000 km. 16 Provincial monetary reimbursement is available for travel greater than 200 km for medical care. Our patient population can also receive subsidized medical transportation for care unavailable in their community, or if their required specialist care is not available within 100 km from their home.…”
Section: Discussionmentioning
confidence: 99%
“…One possible solution for reducing financial costs and school and employment absenteeism is telemedicine or e-medicine follow-up options, 8 16-18 although minimal research exists with respect to telemedicine in pediatric surgery. 16 In other surgical specialties using telemedicine, patient's families and surgeons have reported satisfaction with the system along with a decreased financial burden. 8 Telehealth and e-consult are both available for use by physicians in Manitoba; however, there is no mention of their use in our studied population.…”
Section: Open Accessmentioning
confidence: 99%